The Insurance Sector in the Middle East and North Africa : Challenges and Development Agenda - Lester, Rodney (2012)
This paper studies the causes of the low development of the insurance sector in the Middle East and North African (MENA) region, particularly for long term insurance. The paper shows that life and non-life premiums, as well as assets, are very low relative to expected levels given per capita income and demographic characteristics, and examines the causes of such poor performance. There is a wide range of factors constraining the development of the industry, including the absence of mandatory insurance in key areas, the predominant presence of the state in some countries, gaps in regulation and supervision, unsupportive tax regimes, fragmented market structures, a chronic lack of suitably skilled people, as well as the absence of products that conform with cultural/religious preferences, especially in the case of life insurance. The lack of development of the insurance sector is a matter of concern, as research shows that the sector can contribute to both financial and economic development. Key recommendations to accelerate the development of the sector include wider introduction of mandatory insurance lines that have clear positive externalities, continuing the privatization process for government owned insurers, employing non capital techniques to force rationalization of insurance sectors with too many small and inefficient players, removing tax distortions, taking steps to stabilize motor third party liability markets (typically the largest line of business), strengthening reporting and disclosure, regulating banc-assurance, improving consumer protection, further developing Takaful long term insurance ('Family Insurance'), and establishing regional centers of excellence for skills development.